Aggression toward Familiar People, Strangers, and Conspecifics in Gonadectomized and Intact Dogs - Farhoody, Parvene; Mallawaarachchi, Indika; Tarwater, Patrick M.; Serpell, James A.; Duffy, Deborah L.; Zink, Chris (Frontiers in Veterinary Science, 2018)
Gonadectomy is widely used to treat and prevent behavior problems including aggression in dogs. The aim of this study was to determine whether aggressive behavior toward familiar people, strangers, or other dogs was significantly different in dogs gonadectomized at various ages vs. intact dogs using the Canine Behavioral Assessment Research Questionnaire (C-BARQ) was used with multivariate analysis. Of 15,370 initial surveys, those for dogs reported to have been gonadectomized at less than 6 weeks of age or to correct a behavior problem, and those with incomplete answers to questions regarding independent or dependent variables were excluded, leaving 13,795 for analysis of aggressive behavior toward familiar people, 13,498 for aggressive behavior toward strangers, and 13,237 for aggressive behavior toward dogs. Aggressive behavior was defined a) using mean scores for all questions on the C-BARQ for aggressive behavior (range 0 to 4), and b) comparing dogs with no aggressive behavior (all questions answered 0) to dogs with moderate or severe aggression (at least one score of 2, 3, or 4). Data for intact dogs were compared to those for dogs gonadectomized at 6 months or less, 7 -12 months, 11 - 18 months, and > 18 months. Neither gonadectomy nor age at gonadectomy showed an association with aggression toward familiar people or dogs. There was a low but significant increase in the odds of moderate or severe aggression toward strangers for gonadectomized dogs as compared to intact dogs. This was encompassed entirely by data for dogs gonadectomized at 7 - 12 months of age; these dogs were 26% more likely to demonstrate aggression toward strangers. This large, comprehensive study of the relationships between gonadectomy and aggressive behavior in dogs demonstrates that when the many factors affecting aggressive behavior are considered, there is no evidence that gonadectomy at any age alters aggressive behavior toward familiar people or strangers, and only a minimal increase in aggression toward dogs. Given increasing evidence of significant negative health effects of gonadectomy, there is an urgent need to systematically examine other means of preventing unwanted procreation, such as vasectomy and hysterectomy.